Struktur Komunitas Vegetasi Mangrove Berdasarkan Karakteristik Substrat di Taman Hutan Raya Ngurah Rai, Bali - Ni Kadek Dian Prinasti; I Gusti Bagus Sila Dharma; Yulianto Suteja (Journal of Marine and Aquatic Sciences, 2020)
Mangrove is a typical type of vegetation found in tropical beach areas. Mangrove forests as one of the potential natural resource that is utilized by the community. Excessive utilization of mangrove forest and not offset by rehabilitation will lead to a decrease in mangrove area which causes reduced mangrove function in the ecosystem. One of the factors affecting mangrove growth is soil or substrate. In general, mangrove forest areas are present throughout the Indonesian coast and are grown in locations that are still influenced by tidal activity. The largest mangrove forest destruction in Bali occurred in the area of Tahura Ngurah Rai, which is 253.4 hectares of total area of 1,373.5 hectares. The purpose of this research is to know the structure of the mangrove community based on the characteristics of the substrate at Taman Hutan Raya Ngurah Rai, Bali. Data collection using line transect method and analyzed quantitatively by using INP analysis. From five research stations, nine mangrove species are found, including Sonneratia alba, Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorhiza, Bruguiera sexangula, Xylocarpus granatum, Avicennia lanata, Avicennia officinalis and Aegiceras floridium. The substrate component in TAHURA is dominated by sand followed by clay and mud. Species Sonneratia alba and Rhizophora apiculata are found in all types of substrates, Rhizophora mucronata species found in two substrate types, sandy loam substrates and sandy clay, but some species are found only in one type of substrate such as Xylocarpus granatum, Avicennia lanata, Avicennia officinalis, Bruguiera gymnorhiza and Bruguiera sexangular.